TYPES OF TRANSLATION USED IN THE BATAK TOBA - INDONESIAN TRANSLATION OF SONG “Aut Boi Nian” - Fitri Ervina Tarigan (Jurnal Dialect, 2025)
This research centered on analyzing types of translation used in the Batak Toba-Indonesian Translation of Song “Aut Boi Nian”. The primary objective of the research was to investigate the types of translation existed in Aut Boi Nian Song’s translation such as literal translation,free translation,idiomatic translation, ethnographic translation. This study employed a descriptive qualitative research methodology. The data were gathered from the Batak Toba-Indonesian translation  lyrics.  In this research, the data would be the song lyrics and the translation which have 18 sentences. The most dominant type used in the song lyrics was free translation with 66,667 % from the total of percentages. And the least dominant type was idiomatic translation with only 5.6% distribution to the total number of percentages. Based on the findings, it was indicated that free translation assist the audience conserve the emotional power of the lyric instead of its literal structure and also ensured that listeners feel the same way as the source audience by making sure that both pragmatic and affective meanings were same. The results contribute to the development of translation process,translation strategies, discourse analysis of another regional language text.